Analysis of Students' Physics Numeracy Literacy Ability and Its Learning Implementation: Case Study in Nganjuk City - Sunarti, Titin; Wasis, W; Setyarsih, Woro; Zainuddin, Abu; Jauhariyah, Mukhayyarotin Niswati Rodliyatul; Zakaria, Azar; Rizki, Iqbal Ainur (Studies in Learning and Teaching, 2024)
This study aims to identify high school students' numeracy literacy abilities and physics learning that trains numeracy literacy. The study involved 183 students from three high schools (SMAN A, B, and C) in Nganjuk district, along with 9 teachers. Research instruments included a Numeracy Literacy Test and Physics learning response questionnaire, both validated by experts. Results showed that students' literacy skills were high (81.5%), with interpretation and integration scoring highest (90.33%), followed by information finding (77.33%) and evaluation/reflection (77.13%). In numeracy abilities, understanding scored highest (88.47%), followed by application (72.37%) and reasoning (63.9%). The reliability analysis of the research instrument showed a Cronbach's Alpha value of 0.87, indicating very good internal consistency in measuring the literacy-numeracy skills of high school students in Nganjuk Regency. This high reliability value provides a strong level of confidence in the research findings, including the average literacy skills (81.5%) and numeracy (78.25%). The overall average numeracy ability was 74.91%, falling in the sufficient category. Common teaching approaches included explanation with example problems, practice questions, and practicals (55%), along with the 5M approach (observe-question-try-analyze-communicate) used often (44.4%) or always (33.3%). Popular learning models included Direct Instruction (55.5%), Cooperative Learning (44.4%), Inquiry (22.2%), Problem-Based Learning (33.3%), and Project-Based Learning (66.6%). Other models included Discovery learning, Cooperative game learning, and differentiated PjBL. In conclusion, students' numeracy literacy ability reached a sufficient level at 78.5%.